RANCANG BANGUN SISTEM PEMINJAMAN PERLENGKAPAN EVENT MENGGUNAKAN METODE TOPSIS DI UNIVERSITAS HASYIM ASY’ARI JOMBANG - Maulana , Syahrul; Imam Agung , Achmad; Ali , Mahrus (Inovate, 2024)
Universitas Hasyim Asy'ari has 31 active student organizations that organize various events for students and public. However, university faces conflicting requests for a simultaneous use of facilities and equipment for these events. Therefore, research aims to develop a system using TOPSIS method to assist equipment administrator in making decisions for allocation of facilities and equipment. This research is focuses on designing and implementing a system for borrowing facilities and equipment for events at Universitas Hasyim Asy'ari, while also investigating how to effectively apply TOPSIS method within this system. TOPSIS method is utilized to prioritize events based on specific criteria, such as estimated number of participants, speakers or guests, and event costs. This method selects alternatives that are closest to positive ideal solution and farthest from negative ideal solution. Research findings demonstrate that manual calculation of TOPSIS method aligns with results obtained from system implementation, generating identical values for each evaluated alternative. implementation of TOPSIS method in this system has been carried out accurately, and system gives results corresponding to manual calculations. This increases confidence in results of evaluation and selection of alternatives for borrowing facilities and equipment in organizing events. Keywords: Facility and Equipment Rental System, Event, TOPSIS Method.